Genomic profiling of methicillin-sensitive Staphylococcus aureus (MSSA) isolates in Kuwait hospitals - Boswihi, Samar S.; Alfouzan, Wadha A.; Udo, Edet E. (Frontiers in Microbiology, 2024)
Staphylococcus aureus is an important pathogen that causes mild to invasive infections in hospitals and in the community. Although methicillin-susceptible Staphylococcus aureus (MSSA) isolates continue to cause different infections, there are no data on the genetic backgrounds of the MSSA colonizing or causing infections in Kuwait hospitals. The aim of this study was to investigate MSSA isolated from patients in Kuwait hospitals for antibiotic resistance and genetic backgrounds to understand their clonal composition. Consecutive MSSA isolates from single patients were collected during two surveillance periods in 2016 and 2021 in 13 public hospitals. The isolates were characterized using antibiogram, staphylococcal protein A (spa) typing, DNA microarray analysis, and multilocus sequence typing (MLST) using standard protocols. A total 446 MSSA was cultured from different clinical samples in 2016 (n=240) and 2021 (n=206). All isolates were susceptible to vancomycin (MIC ≤ 2 mg/L), teicoplanin (MIC ≤ 2 mg/L), linezolid (MIC ≤ 4 mg/L), ceftaroline (MIC ≤ 2 mg/L), rifampicin and mupirocin but were resistant to erythromycin (21.3%), clindamycin (14.0%), gentamicin (3.8%), kanamycin (10.5%), fusidic acid (27.0%), tetracycline (6.9%), trimethoprim (23.1%), and ciprofloxacin (35.2%). Molecular typing identified 155 spa types, dominated by t127 (15.0%), t084 (5.4%), t3841 (5.4%), t267 (2.4%), t442 (2.2%), t091 (2.2%), t021 (2.2%), and t003 (2.2%); 31 clonal complexes (CCs), and 56 sequence types (STs). Most of the isolates (n=265; 59.4%) belonged to CC1 (20.6%), CC15 (10.9%), CC22(5.1%), CC30 (7.6%), CC361 (10.1%) and CC398 (4.7%). The MSSA isolates belonged to diverse genetic backgrounds dominated by CC1, CC15, CC22, CC30, CC361, and CC398. The distribution of MSSA clones in 2016 and 2021 showed stability of these clones overtime. The study provides the first comprehensive data on the clonal distribution of MSSA in Kuwait hospitals.